Efficacy and Safety of Pancrelipase/Pancreatin in Patients With Exocrine Pancreatic Insufficiency and a Medical History of Diabetes Mellitus. Issue 5 (May 2016) - Whitcomb, David C.; Bodhani, Amit; Beckmann, Katrin; Sander-Struckmeier, Suntje; Liu, Shufang; Fuldeore, Mahesh; Pollack, Paul F.; Khurmi, Rupal P.
Abstract : Objectives: The aim of this study was to perform exploratory analyses of the efficacy and safety of pancrelipase delayed-release capsules (Creon) in patients with exocrine pancreatic insufficiency (EPI) with (n = 36) and without (n = 18) concurrent diabetes mellitus (DM). Methods: This was a retrospective, post hoc, subgroup (±DM) analysis of a double-blind, randomized, placebo-controlled trial of pancrelipase in patients with EPI due to chronic pancreatitis or pancreatectomy (total or partial). After a 5-day placebo run-in period (baseline), patients were randomized to pancrelipase (72, 000 lipase units/meal, 36, 000/snack) or placebo for 7 days. Outcomes included changes in coefficients of fat absorption (CFA) and nitrogen absorption (CNA) from baseline to the end of the double-blind period. Results: Mean changes in nutrient absorption were greater with pancrelipase versus placebo in patients with DM (CFA, 36.0% vs 7.5%, P < 0.0001; CNA, 33.4% vs 3.7%, P = 0.0002) and without DM (CFA, 25.2% vs 12.3%, P = 0.0326; CNA, 39.1% vs 17.6%, P = 0.1187). Diabetes mellitus was not significantly associated with outcomes for CFA ( P = 0.0802) and CNA ( P = 0.2934). Incidences of adverse events, including hypoglycemia and hyperglycemia, were similar in the pancrelipase and placebo arms. Conclusions: Pancrelipase improved fat and protein absorption in patients with EPI due to chronic pancreatitis or pancreatectomy, with or without DM, and matched the safety profile previously reported.